THE IMPACT OF VIRTUAL REALITY ON SELF-ACTUALIZATION OF TEENAGERS: ANTHROPOLOGICAL DIMENSION - S. V. Storozhuk; Y. N. Goyan (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Mechanization and computerization of modern society causes dramatic changes in the forms and methods of teaching. Their uniqueness lies in bringing computer technology and the Internet for education, causing formation of extreme polar social assessments of their impact on the harmonious development of children and adolescents, on possibility of self-actualization of natural potentials of teenagers whose minds are often on the brink of real and virtual worlds. Methodology is caused by interdisciplinary approach, involving not only the use of scientific methods such as analysis, synthesis and generalization, but also the methods of comparative analysis and analogies which were used to solve specific research problems related to the study of influence of computer technology and created through it virtual reality on self-actualization of teenagers. Originality lays in the explication of conceptual philosophical core to study the impact of virtual reality on self-actualization of teenagers and to prove possibility of differentiation of such concepts as "actualization" and "self-actualization" for the study of specific features of teenagers’ development. Such the approach provides a theoretical justification of major conflicts of personality development in adolescence and clearly demonstrates the threats that virtual reality brings to the process of person formation and development of mankind. Conclusions. Due to high levels of emotional stress in teenagers’ worldview, there is no evidence to suggest that they are at the level of self-actualization. The latter is possible only in the case of organic inclusion of adolescents in real socio-cultural processes, while their simulation in the virtual world can lead to inhibition of personality development.